Political reform in Iran during Khatami Presidency, 1997- 2005 - Asayesh, Hossein (2017)
In the present study, the researcher attempted to unfold the process of political reform in Iran during Khatami presidency from 1997 to 2005. It analysed the political reform during Khatami’s administration. Second, the study investigated factors affecting the growth of political parties during the reformation era of President Khatami, and finally, it rendered several strategies and recommendations to overcome the factors and problems hindering the growth of political parties from 1997 to 2005. The research employed qualitative approach, where primary data were collected through indepth interviews involving 14 informants using purposive sampling frame. They were among Iranian party leaders. The data were analysed manually and content analysis was used to analyse secondary data gathered from related literature. The findings indicated that Khatami ignited several reformation programs that gradually aided the growth of political parties from 1997 to 2005, but unfortunately most of the programs were unsuccessful mainly because he gained less support and acceptance from the Supreme Leader. The findings also showed that there were certain factors affecting the growth of political parties, namely electoral system, party law, party funding, and cultural component. Next, all informants provided valuable inputs in terms of establishing underlying strategies and providing valuable suggestions for the empowerment of political parties. Additionally, the findings provided in-depth understanding about the reformation process of political parties undertaken by President Khatami from 1997 to 2005. The present study is hoped to promote better understanding and add knowledge in the area of political reform. Finally, the study presented some recommendations for further research regarding this topic.